Pancasila Perspective on the Interpretation of Peci as Symbolic Communication in Indonesian Culture - Cici Anggraini; Muhammad Alfikri (PT Mattawang Mediatama Solution, 2022)
The purpose of this article is to learn how Pancasila interprets and views the cap as a part of Indonesian culture. The Indonesian people have been known for their rich culture since ancient times, and foreign countries regard Indonesia as a colorful country. From a historical standpoint, there is an outfit that serves as a symbol of communication, namely the cap. Because it appeared ancient and not modern, the cap was initially regarded as a symbol of discrediting the Indonesian people. Later, as a symbol of equality, Indonesian politicians began to wear the cap. This study employs the descriptive analysis method in conjunction with a literature review. According to the findings of this study, the cap symbol represents Pancasila values such as divinity, humanity, unity, democracy, and justice. The cap is a symbol of equality that forms a pattern. This pattern represents the balance of degrees, humanity, the law, and social life. The cap has a significant impact on people's perceptions and behavior.